The research and development centers and their duties in developing the suitable environment for measuring researches abilities (Al-Mansour Journal, 2023)
To make a correct basics to guarantee the ways for obtaining the technology and to acquire the scientific knowledge are represented in developing and flourishing the research and development centers. In order to promote the capabilities for preparing researches through making arrogation principles and labor division to insure encouragement and comprehension of spreading the technology. Hence, and in the light of steering the strategic design, in order to achieve social and economic development which required by the stage necessities.